A study on postgraduate student evaluation on coursework and research by using fuzzy analytical hierarchy process / Nur Najihah Shahrani - Shahrani, Nur Najihah (2018)
There are many postgraduate programs offered in Malaysia at every university whether in public or private university. Students can choose whether to pursue their studies or not after completing the undergraduate study. If they choose to pursue their postgraduate study, they can choose their study approach whether it is coursework or research. Thus, the problem arises. Most students wishing to pursue postgraduate studies have a problem whether to choose coursework or research. Hence, to solve this problem, Fuzzy Analytical Hierarchy Process (FAHP) method has been used. In this research, seven main criteria and each sub criteria are used to study the suitability of students to pursue at the postgraduate level in order choose their study approach and the results shown whether student tends to research or coursework.